AI, Emotions, and Interaction: A Social Matching System with ChatGPT-Based Conversational Agents - Bucior, Lucas; Plentz, Patricia Della Méa (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS); 2025: Anais da I Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul, 2025)
This article presents the development and evaluation of Tiander, an experimental platform inspired by dating applications, aimed at investigating the interaction between humans and artificial intelligence agents. The system was implemented as a web application, supporting simulated profiles operated by conversational assistants based on ChatGPT. For experimental purposes, two versions were created, one with dynamic AI-generated responses and the other with fixed responses that mimic limited human interactions. The sample will consist of (N) participants, randomly divided between the two groups, who will interact with male or female profiles according to their initial choice. At the end of the experience, participants will answer a questionnaire assessing aspects such as perceived authenticity, empathy, trust, and humanity attributed to the interaction. The proposal contributes to contemporary debates on ethics, interactive system design, and the role of intelligent assistants in social and affective contexts. The data obtained will allow for an empirical analysis of users’ perception regarding different levels of simulated intelligence, broadening the understanding of AI’s impact in interpersonal interaction environments.